Therapeutic management and evolution of chronic hepatitis B: does HIV still have an impact? The EPIB 2012 study. (22nd January 2015) - Piroth, Lionel; Pol, Stanislas; Miailhes, Patrick; Lacombe, Karine; Lopes, Amanda; Fillion, Aurélie; Loustaud‐Ratti, Véronique; Borsa‐Lebas, Françoise; Salmon, Dominique; Rosenthal, Eric; Carrat, Fabrice; Cacoub, Patrice; et al.
Abstract Background & Aims To compare the management of chronic hepatitis B (CHB) and its evolution over time in currently followed HIV‐positive and HIV‐negative patients. Methods A total of 709 consecutive patients with past or present positive HBs antigenemia seen in October 2012 in 19 French participating centres were included. The data were retrospectively collected from the first visit onwards through standardized questionnaires. Results Chronic hepatitis B was less often assessed in the 299 HIV‐positive patients, who were older, more likely to be male, excessive alcohol drinkers and HBe antigen‐, HCV‐ and HDV‐positive. They were also followed up for a longer time (11.3 +/−8.8 vs. 8.6 +/−6.9 years, P < 10−3) and were more frequently treated for HBV (95.3% vs. 56.8%, P < 10−3). HBV was undetectable at the last visit in 80.8% of HIV‐positive vs. 55.1% of HIV‐negative patients (P < 10−3). In multivariate analyses, undetectable HBV was significantly associated with older age, lower baseline HBV DNA, longer HBV therapy and no previous lamivudine monotherapy, but not with HIV. Cirrhosis was associated with age, male gender, Asian origin, alcoholism, HCV, HDV, but not with HIV infection. Hepatocellular carcinoma, less frequently observed in HIV‐positive patients (0.7% vs. 4.7%, P = 0.002), was positively associated with age, male gender, cirrhosis and negatively associated with HIV infection (OR 0.15, 95%CI 0.03–0.67, P = 0.01). Conclusions Although the assessment of CHB still has to be improved in HIV‐positive patients, the negative impact of HIV on the virological, histological and clinical evolution of CHB seems to be disappearing, probably because of the immunovirological impact of HAART and the more frequent and longer use of HBV therapy.